Роль вікової диференціації в цифровому маркетингу - Халявка, Юлія; Вовк, Наталія (Видавництво Львівської політехніки, 2025)
The article explores the importance of age differentiation in the development and implementation of SMM strategies. It defines the content consumption characteristics of different age groups, including their preferences regarding platforms, content formats, communication styles, and interaction with influencers. The study analyzes how digital literacy, information processing pace, and trust in sources affect the effectiveness of social media promotion. Special attention is given to the practical aspects of content adaptation for various generations, including message personalization and multicomponent campaign design. A table is provided outlining the features of age groups to optimize communication approaches. The paper highlights the importance of flexibility, continuous monitoring, and ongoing analysis in achieving sustainable marketing results.
Keywords: соціальні мережі; вікова диференціація; SMM-стратегія; цифровий маркетинг; цільова аудиторія